Therapeutic approach to the management of HER2-positive breast cancer metastatic to the brain. Issue 2 (28th March 2015) - Patil, Ajay; Sherbet, G.V.
Highlights: This article concerns the ability of HER2 positive breast cancers to metastasise specifically to the brain. This is an important topic in cancer management and my colleague and this article provide an up-to-date account stating the current position relating to the problem and highlights new insights into tackling the problem especially in relation to patient management. Abstract: HER2 positive breast cancers have been shown to have a greater propensity to metastasise to the brain. This may be due to several reasons, including the creation of a "sanctuary-site" for tumour in the brain following trastuzumab therapy. Elucidating the mechanism of this phenomenon may aid the prevention or intervention and treatment of such metastases, but research is limited by the deficiency and diminished access of CNS tissue. However, CNS penetrable HER2 receptor antagonists such as lapatinib and intrathecal administration of trastuzumab might benefit patients, and are worthy of further investigation. New avenues of molecular approach have focused on manipulating signal transduction system involved in HER2 function. The importance of systemic therapies and those targeted to metastatic lesions is emphasised and evaluated here.